Privatization in Sri Lanka - Dissanayake, Kasun (Kansas State University, 2012)
This report examines the role of the privatization in Sri Lanka and assesses its effectiveness. The focus was given for the evolution of privatization and how socio-political factors such as rent-seeking, inconsistency policy making, market competition, political uncertainty and role of supporting institutions have affected the privatization process. After the independence in 1948, several reforms have been taken place in Sri Lanka. In 1977, a market oriented policy package which brought huge amount of foreign aids into the country was introduced. Further the privatization in Sri Lanka can be addressed as: Sporadic attempt, Systematic approach and Structured approach. The appointment of short-term governments and changing of the leadership has always been a hurdle for a successful privatization in Sri Lanka. In order to establish a successful privatization, it requires having the changing of ownership from public sector to private sector, creating a competitive market environment and forming a proper institutional framework. Unfortunately, due to less emphasis was given to the latter two factors: the privatization has always given undesirable outcomes. In the whole history of privatization in Sri Lanka, the highest value for Foreign Direct Investment (FDI) was recorded in 2008. It is clear that the reason for the FDI value escalation in 2008 is the improved confidence of foreign investors by addressing security concerns. In conclusion, it is time to investigate whether the current regulatory model is the most appropriate arrangement for the prevailing economic, social and cultural circumstances in Sri Lanka.
Keywords: Privatization; Telecommunication; Regulation; Rent-seeking; Foreign direct investment; Sri Lanka; Economics (0501)